IMPROVEMENT QUALITY MANAGEMENT OF EDUCATOR AND EDUCATIONAL STAFF IN THE IMPLEMENTATION OF CURRICULUM 2013 - Madjid, Abdul; Sonhadji, Ahmad; Imron, Ali; Arifin, Imron (IJRDO- Journal of Educational Research, 2017)
The purpose of this research is to find out how to improve the quality of education and education personnel on the implementation of Curriculum 2013 (in the SMAN 3, MAN 3 and SMKN 4 Malang), both in planning, organizing, implementation, and monitoring and evaluation aspects. The approach used in this research is qualitative research method, which aims to comprehend phenomenon or social phenomenon comprehensively and contextually by describing empirical reality about management of quality improvement of education and educational staff on the implementation of Curriculum 2013 in SMA/MA/SMK Negeri Malang. Data collection techniques are through indepth interview mechanism, participatory observation and documentation analysis as well as multicasus data analysis, in individual cases and/or crosscases analysis cases. The study found that the management of quality improvement of educators and educational personnel in the implementation of Curriculum 2013 in SMA/MA/SMK Negeri Malang, including planning, organizing, implementation, monitoring and evaluation in the field of (a) training; (b) development; and (c) mentoring.